From Tweets to token sales: Assessing ICO success through social media sentiments - HUANG, Donghao (Institutional Knowledge at Singapore Management University, 2024)
With the advent of social network technology, the influence of collective opinions has significantly impacted business, marketing, and fundraising. Particularly in the blockchain space, Initial Coin Offerings (ICOs) gain substantial exposure across various online platforms. Yet, the intricate relationships among these elements remain largely unexplored. This study aims to investigate the relationships between social media sentiment, engagement metrics, and ICO success. We hypothesize a positive correlation between favorable sentiment in ICO-related tweets and overall project success. Additionally, we recognize social media engagement indicators (mentions, retweets, likes, follower counts) as critical factors affecting ICO performance. Employing machine learning techniques, we conduct sentiment analysis on tweets, discerning emotional nuances and categorizing expressions as positive or negative. Employing established classification methods, we further analyze engagement data to reveal its impact on ICO interest and awareness. Our research findings offer insights into the predictive potential of social media strategies for ICO success and underscore the importance of investor sentiment and engagement in the volatile cryptocurrency landscape. These insights provide actionable guidance for aspiring crypto founders in formulating effective business development strategies. The source codes and datasets of this paper are accessible at GitHub: https://github.com/inflaton/Success-Indicators-of-Initial-Coin-Offerings.